Synaptic inhibition controls transient oscillatory synchronization in a model of the insect olfactory system - Assisi, Collins; Bazhenov, Maxim (Frontiers in Neuroengineering, 2012)
In a variety of neuronal systems it has been hypothesized that inhibitory interneurons corral principal neurons into synchronously firing groups that encode sensory information and sub-serve behavior (Buzsáki and Chrobak, 1995;Buzsáki, 2008). This mechanism is particularly relevant to the olfactory system where spatiotemporal patterns of projection neuron activity act as robust markers of odor attributes (Laurent et al., 1996;Wehr and Laurent, 1996). In the insect antennal lobe, a network of local inhibitory interneurons arborizes extensively throughout the antennal lobe (Leitch and Laurent, 1996) providing inhibitory input to the cholinergic projection neurons. Our theoretical work has attempted to elaborate the exact role of inhibition in the generation of odor specific projection neuron responses(Bazhenov et al., 2001a;Bazhenov et al., 2001b;Assisi et al., 2011). In large-scale antennal lobe (AL) network models we characterized the inhibitory sub–network by its coloring (Assisi et al., 2011) and showed that it can entrain excitatory projection neurons to the odor specific patterns of transient synchronization. In this focused review, we further examine the dynamics of entrainment in more detail by simulating simple model networks in various parameter regimes. Our simulations in conjunction with earlier studies point to the key role played by lateral (between inhibitory interneurons) and feedback (from inhibitory interneurons to principal cells) inhibition in the generation of experimentally observed patterns of transient synchrony.